Clinical criteria for integrated molecular pathology in intraductal papillary mucinous neoplasm: less is more. Issue 5 (May 2019) - Simpson, Rachel E.; Cockerill, Nathan J.; Yip-Schneider, Michele T.; Ceppa, Eugene P.; House, Michael G.; Zyromski, Nicholas J.; Nakeeb, Attila; Al-Haddad, Mohammad A.; Schmidt, C.M.
Abstract: Background: For pancreatic cysts with negative cytology, Integrated Molecular Pathology (IMP) is a malignancy risk score integrating clinical criteria with pancreatic cyst fluid DNA profiling. Aside from main pancreatic duct (MPD) diameter, integrated clinical criteria are not International Consensus Guidelines High-Risk Stigmata. We predicted exclusion of clinical criteria except MPD diameter could simplify the IMP and better distinguish invasive/malignant disease. Methods: Records of >1100 patients with IPMN were reviewed retrospectively. Sensitivity, specificity, and accuracy of conventional IMP for invasive / malignant disease was compared to DNA profile including only MPD ≥10mm (IMP-10.) Invasive outcomes were invasive-IPMN/adenocarcinoma on surgical pathology, pathologic or radiographic evidence of invasive/metastatic disease during surveillance. Malignant outcomes included high grade dysplastic IPMN (HGD-IPMN). Results: 225 patients who met study criteria underwent 283 IMP evaluations: 98 followed by surgery, 185 followed by ≥ 23 months surveillance. IMP-10 had greater specificity (90.1% vs. 73.7%) and accuracy (89.8% vs. 74.2%) for invasive disease compared to IMP in surgery + surveillance patients, but lower sensitivity (77.8% vs. 88.9%). Trends were similar in surgery patients alone and malignant outcome analyses. Conclusion: IMP-10 excludes less-reliable clinical factors resulting in greater accuracy in predicting invasive / malignant disease and fewer patients with benign disease being recommended for surgery.